The role of science in law - Feldman, Robin (New York ; Oxford : Oxford University Press, 2009)
This work argues that problems at the intersection of law and science flow not from the changing nature of science, but from the changing nature of law. It uses examples from doctrines related to abortion, gene patenting, copyright, and more, to explore the nature of law.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Science and law -- United States; Technological innovations -- Law and legislation -- United States